Ácido cítrico como melhorador da atividade da fitase em aves comerciais - Vieira, Bruno Serpa (2018)
The use of phytases and the consequent reduction in dietary phytates brought great benefits for poultry production. However, the efficacy of phytases in the hydrolysis of these components is still low under gastrointestinal conditions, so a significant amount of phytates remain intact in the diet even after enzymatic supplementation. Phytate and phytic acid are considered important antinutritional factors for poultry. Some studies suggested positive effects of organic acids on phytase activity; nevertheless, controversial results still prevent specific recommendations for the combined use of these additives. Thus, the objective of this thesis was to compare the effects of dietary supplementation of phytase, alone or in combination with citric acid, on productive performance, bone development and mineral metabolism of phosphorus-restricted birds. For this, a systematic review of the literature with meta-analysis was performed for broilers and a field trial was conducted with Japanese quails during the growing phase. Data from the meta-analytical study showed that the combined use of phytase and citric acid induces higher weight gain and bone mineralization in broilers when compared to the supplementation of phytase alone. Besides, we could also conclude that part of the difficult of individual studies in detecting positive effects of this combination might be associated with the short period of phosphorus restriction imposed on birds and/or dietary concentrations of phytase, citric acid and phytate phosphorus under investigation. In agreement with these findings, the field trial proved that the combination of phytase and citric acid, different than the supplementation of phytase alone, inhibits the negative effects of severe (65%) phosphorus restriction in quails. Under moderate (45%) phosphorus restriction, however, no differences between the supplementation of phytase alone or in combination with citric acid were detected. In conclusion, the combined use of phytase and citric acid is an interesting approach and should be better explored by producers as a tool to reduce dietary inclusion of rock phosphates and phosphorus excretion through manure.